RUANG LINGKUP PSIKOLOGI KRIMINAL DAN METODE STUDI KRIMINOLOGI - Arsalan Ayri Fath; Eha Amelya Suherman; Kayla Rahayu Putri; Salsabilla Citra Dwi Rahmadani; Zahwa Kania Putri; Tugimin Supriyadi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
Criminal psychology is a branch of applied psychology that examines the relationship between the psychological characteristics of criminals and the factors that influence the emergence of criminal acts, both from personal, social, and situational aspects. The discussion includes main theories such as Social Learning Theory, Rational Choice Theory, and Psychoanalysis Theory, which are used to analyze the motivation and causes of criminal behavior. The method used in this research is a literature study with a thematic analysis approach, which examines various theories and practices based on relevant sources. The case study highlights the importance of psychological analysis in understanding the drivers of criminal behavior and the influence of the environment on the formation of deviant behavior.